“And more than hundred thousands of troops are with me…”. Military science of the Crimean Khanate during the Modern Times: the review of A. A. Sheykhumerov’s monograph Army of the Crimean Khanate: the organization and tactics (XV–XVIII centuries). Kazan – Simferopol: Sh. Marjani Institute of History of Tatarstan Academy of Sciences, 2019. – 304 p. - Vitaly Penskoy (Крымское историческое обозрение)
A study “The Army of the Crimean Khanate” of a young Crimean historian A. A. Sheykhumerov was published last year. It is devoted to the Crimean Khanate’s warfare in Modern Times (XV–XVIII centuries). The purpose of work, chosen by the author, is not clearly related to the number of popular and actively developed by domestic historical science topics. As the basic topic of research the historian took this problematic method and concentrated on analyzing key stories from the history of the Crimean warfare development in the New Times. This book in modern Russian historiography is the first essay on warfare of the Crimean Tatars. It allows us to have a holistic view of its main features and characteristics. The review gives a brief description of the structure and content of work and makes notes of some disputable points in the author’s concept and interpretations of individual moments in the history of the Crimean warfare evolution.